New treatment of the pancreatic cystic neoplasm: Endoscopic ultrasonography-guided radiofrequency ablation combined with lauromacrogol ablation - Feng, Xiuxue; Linghu, Enqiang; Chai, Ningli; Li, Huikai (Turkish Journal of Gastroenterology, 2018)
Abstract Pancreatic cystic neoplasms (PCNs) are being increasingly detected because of rapid advances in radiologic technology and an increased imaging demand. The management of PCNs is challenging as most of these neoplasms are asymptomatic, but have malignant potential, and surgical resection has substantial perioperative morbidity and mortality. Endoscopic ultrasonography (EUS)-guided ablation, as a minimally invasive treatment, has received increasing attention in the past few years. However, the resolution after EUS-guided ablative therapy still needs to be improved. In this case report, EUS-guided radiofrequency ablation combined with lauromacrogol ablation was applied for the first time in the treatment of PCN, and it showed complete resolution at a 3-month follow-up. Cite this article as: Feng X, Linghu E, Chai N, Li H. New treatment of the pancreatic cystic neoplasm: Endoscopic ultrasonography-guided radiofrequency ablation combined with lauromacrogol ablation. Turk J Gastroenterol 2018; 29: 97-100.